Metsän illuusio:Installaatio (kierrätyspaperi, puurima, puupelletti) - Huhmarniemi, Maria (Stormen Concert Hall, 2024)
The installation consists of elements handmade recycled paper. It has resulted from the art project ‘Observation of Change’, which collaborates with a nature restoration project in the Junkerdal area, Saltdal municipality, Norway. This project addresses the complex issues of forest biodiversity. Restoration involves cutting down spruce forests to make space for a more original and natural ecosystem. While some people perceive this restoration process as wasteful or even harmful to trees, similar attitudes are often not encountered in the wood industry, which involves massive clear-cutting of forests. This paper sculpture installation aims to depict human-forest relations, highlighting how they are deeply influenced by utilitarian values. Art installation aims to evoke questioning on forests as something that should serve primary human needs and economy. The general attitude of seeing the forests as an asset should be changed.